Development of honey bees in hives with different colors and covering materials in the Brazilian semiarid (Research, Society and Development, 2020)
This study aimed to verify the influence of different colors and covering materials in Langstroth hives by analyzing the development of honey bees (Apis mellifera). The experiment was conducted in an experimental apiary in Petrolina (Pernambuco State, Brazil).  Twenty-four hives were used, arranged in a completely randomized 3 x 2 factorial design (three colors and two types of cover). The development of the colonies was analyzed through a mapping of the nest frames and measurements of the internal temperature of the hives, then an area count containing honey, pollen, worker cells (closed and open) and drone cells was performed. The results indicate that in traditional hives (unpainted) or painted white, with and without the plasterboard under its lid, there is a greater storage of pollen and honey, in addition to the largest area with cells of worker bees. Already in Langstroth boxes painted blue, there is an increase in internal temperature in the hive, with a larger area of drone cells. In this way, keeping the hives with light colors and protect them with plaster is an alternative to avoid excessive increase of the internal temperature in the hives.